2011
DOI: 10.1016/j.neuron.2011.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Neural Synchronization in Toddlers with Autism

Abstract: Summary Autism is often described as a disorder of neural synchronization. However, it is unknown how early in development synchronization abnormalities emerge and whether they are related to the development of early autistic behavioral symptoms. Here, we show that disrupted synchronization is evident in the spontaneous cortical activity of naturally sleeping toddlers with autism, but not in toddlers with language delay or typical development. Toddlers with autism exhibited significantly weaker inter-hemispher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
291
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 353 publications
(328 citation statements)
references
References 37 publications
24
291
2
5
Order By: Relevance
“…As indicated in Fig 6A and 6B, children with ASD tended to exhibit higher Omega complexities than TD children in many time windows (such as time windows from 0 to 600 ms), which suggests that the former children exhibit reduced whole brain synchronization relative to the latter children. Our results are consistent with several recent reports of reduced brain hemodynamic synchronization in young children, adolescents and adults with ASD [55][56][57][58][59]. Two recent studies reported significantly decreased inter-hemispheric synchronization in toddlers with ASD [55] and in adolescents and adults with ASD [56].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As indicated in Fig 6A and 6B, children with ASD tended to exhibit higher Omega complexities than TD children in many time windows (such as time windows from 0 to 600 ms), which suggests that the former children exhibit reduced whole brain synchronization relative to the latter children. Our results are consistent with several recent reports of reduced brain hemodynamic synchronization in young children, adolescents and adults with ASD [55][56][57][58][59]. Two recent studies reported significantly decreased inter-hemispheric synchronization in toddlers with ASD [55] and in adolescents and adults with ASD [56].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with several recent reports of reduced brain hemodynamic synchronization in young children, adolescents and adults with ASD [55][56][57][58][59]. Two recent studies reported significantly decreased inter-hemispheric synchronization in toddlers with ASD [55] and in adolescents and adults with ASD [56]. Structural imaging has also demonstrated abnormalities in inter-hemispheric long-range white matter pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the rodent studies, there is increasing evidence from both imaging and neurophysiologic studies pointing to altered brain connectivity as a key feature of the pathophysiology of ASD (Casanova and Trippe 2009;Dinstein et al 2011;Kana et al 2011;Muller et al 2011). Additionally, there is some evidence that the changes in neuronal organization in ASD are differentially expressed with age, marked by early life brain overgrowth including increased neuron number, followed by decreases in both structural volumes and neuron number as the brain ages.…”
Section: Aberrant Connectivity In Autismmentioning
confidence: 83%
“…• Geographic area 98 recorded functional MRI activity from 63 naturally sleeping toddlers with ASD, language disorder (ie, standardized score at least 1 SD below the mean), or typical development. Relative to the other groups, toddlers with an ASD exhibited significantly weaker interhemispheric correlations in the inferior frontal gyrus and superior temporal gyrus, 2 areas central to language production and comprehension.…”
Section: Examine the Effectiveness Of Repeat Screeningmentioning
confidence: 99%